Telling the truth: fictionality and epic in seventeenth-century German literature - Werle, Dirk; Korn, Uwe Maximilian (Journal of literary theory, 2020)
Research on the history of fiction of the early modern period has up to now taken primarily the novel into consideration and paralleled the rise of the novel as the leading genre of narrative literature with the development of the modern consciousness of fictionality. In the present essay, we argue that contemporary reflections on fictionality in epic poetry, specifically, the carmen heroicum , must be taken into account to better understand the history of fiction from the seventeenth century onwards. The carmen heroicum , in the seventeenth century, is the leading narrative genre of contemporary poetics and as such often commented on in contexts involving questions of fictionality and the relationship between literature and truth, both in poetic treatises and in the poems themselves. To reconstruct a historical understanding of fictionality, the genre of the epic poem must therefore be taken into account. The carmen heroicum was the central narrative genre in antiquity, in the sixteenth century in Italy and France, and still in the seventeenth century in Germany and England. Martin Opitz, in his ground-breaking poetic treatise, the Buch von der Deutschen Poeterey (1624), counts the carmen heroicum among the most important poetic genres; but for poetry written in German, he cites just one example of the genre, a text he wrote himself. The genre of the novel is not mentioned at all among the poetic genres in Opitz’ treatise. Many other German poetic treatises of the seventeenth century mention the importance of the carmen heroicum , but they, too, provide only few examples of the genre, even though there were many Latin and German-language epic poems in the long seventeenth century. For Opitz, a carmen heroicum has to be distinguished from a work of history insofar as its author is allowed to add fictional embellishments to the ›true core‹ of the poem. Nevertheless, the epic poet is, according to Opitz, still bound to the truthfulness of his narrative. Shortly before the publication of Opitz’ book, Diederich von dem Werder translated Torquato Tasso’s epic poem Gerusalemme liberata (1580); his translation uses alexandrine verse, which had recently become widely successful in Germany, especially for epic poems. Von dem Werder exactly reproduces Tasso’s rhyming scheme and stanza form. He also supplies the text with several peritexts. In a preface, he assures the reader that, despite the description of unusual martial events and supernatural beings, his text can be considered poetry. In a historiographical introduction, he then describes the course of the First Crusade; however, he does not elaborate about the plot of the verse epic. In a preceding epyllion - also written in alexandrine verse - von dem Werder then poetically demonstrates how the poetry of a Christian poet differs from ancient models. All these efforts can be seen as parts of the attempt to legitimate the translation of fictional narrative in German poetry and poetics. Opitz and von dem Werder independently describe problems of contemporary literature in the 1620s using the example of the carmen heroicum . Both authors translate novels into German, too; but there are no poetological considerations in the prefaces of the novels that can be compared to those in the carmina heroica . Poetics following the model established by Opitz develop genre systems in which the carmen heroicum is given an important place, too; for example, in Balthasar Kindermann’s Der Deutsche Poet (1664), Sigmund von Birken’s Teutsche Rede- bind- und Dicht-Kunst (1679), and Daniel Georg Morhof’s Unterricht von der Teutschen Sprache und Poesie (1682). Of particular interest for the history of fictionality is Albrecht Christian Rotth’s Vollständige Deutsche Poesie (1688). When elaborating on the carmen heroicum , Rotth gives the word ›fiction‹ a positive terminological value and he treats questions of fictionality extensively. Rotth combines two contradictory statements, namely that a carmen heroicum is a poem and therefore invented and that a carmen heroicum contains important truths and is therefore true. He further develops the idea of the ›truthful core‹ around which poetic inventions are laid. With an extended exegesis of Homer’s Odyssey , he then illustrates what it means precisely to separate the ›core‹ and the poetic embellishments in a poem. All these efforts can be seen as parts of the attempt to legitimize a poem that tells the truth in a fictional mode. The paper argues that a history of fictionality must be a history that carefully reconstructs the various and specifically changing constellations of problems concerning how the phenomenon of fictionality may be interpreted in certain historical contexts. Relevant problems to which reflections on fictionality in seventeenth-century poetics of the epic poem and in paratexts to epic poems react are, on the one hand, the question of how the genre traditionally occupying the highest rank in genre taxonomy, the epic, can be adequately transformed in the German language, and, on the other hand, the question of how a poetic text can contain truths even if it is invented.